REVIEW ON THE TECHNIQUES OF DIRECTIONAL IDENTIFICATION THROUGH THE CELESTIAL OBJECTS AMONG ANCIENT MUSLIM ASTRONOMERS IN NORTHERN NIGERIA - Bilyaminu Muhammad (Fakultas Syari'ah dan Hukum UIN Walisongo, 2022)
This article aims to reconstruct the old science adopted by ancient Muslim astronomers at that time due to the absence of technology to guide on sea and land. This paper adopts a qualitative method to describe the precise technique and strategy of its application for direction identification through the selection of several Stars, Satellites, Constellations and Coordinate which are visible both from the northern and southern parts of the northern Nigeria sky. On the other hand, several challenges were identified to affect the development of science in different dimensions such as total dependence on artificial innovative devices which may very well have limitations. This article recommends awakening to Astronomers, especially Nigerian Astronomers, to pay more attention to scientific aspects as the basis for the use of modern astronomical technology in every observation of celestial bodies.